Pathological analysis of periprosthetic soft tissue and modes of failure in revision total joint arthroplasty patients. (September 2021) - Bettiol, Patrick; Egan, Alec; Cox, Cameron; Wait, Eric; Brindley, George
Objectives: Implant failure leading to revision total joint arthroplasty can occur through a variety of different mechanisms which are typically associated with a soft tissue response adjacent to the implant that provide insight into the underlying etiology of implant failure. The objective of this study was to elucidate mechanisms of implant failure as they relate to histological classification and findings of adjacent periprosthetic tissue. Methods: Histological analysis of soft tissue adjacent to the implant was performed in 99 patients with an average age of 64 years old and grouped into four categories based on the study conducted by Morawietz et al.: Type I (N = 47) Wear particle induced type Type II (N = 7) Infectious type Type III (N = 19) Combined type I and II Type IV (N = 26) Indeterminant type Modes of failure were categorized into five groupings based on the study conducted by Callies et al.: Instability (N = 35), Aseptic Loosening (N = 24), Hardware and/or Mechanical Failure (N = 15), Septic (N = 13), and Other failures (N = 12). We calculated odds ratios and conducted regression analysis to assess the relationship between modes of failure and histological findings as well as modes of failure and comorbidities. Results: Hardware/mechanical failure was independently correlated with histological findings of anucleate protein debris, histiocytes, Staphylococcus epidermidis, and synovitis. Furthermore, hardware/mechanical failure was independently correlated with osteosarcoma as a co-morbidity. Septic failure was associated with histological findings of Enterococcus, granulation tissue, and tissue necrosis as well as comorbidities of Crohn's disease, deep venous thrombosis, lung disease, and rheumatoid arthritis. Infection was 5.8 times more likely to be associated with Type II histology. Aseptic loosening was associated with histologic findings of synovitis. Conclusion: Our findings support the existing literature on periprosthetic tissue analysis in revision total joint arthroplasty which may improve surgeon understanding of the patholophysiological mechanisms that contribute to implant failure and revision surgery.